Use of botanical extracts to control the aphid (Myzus persicae: Aphididae) and whitef ly (Bemisia tabaci: Aleyrodidae) in pepper crop (Capsicum anuum: Solanaceae), in Ecuador - Vélez-Ruiz, Mayra Carolina; Meza-Vera, Richard Jordan; Abasolo-Pacheco, Fernando; Álvarez-Romero, Pablo Israel (REVISTA TERRA LATINOAMERICANA, 2022)
Botanical extracts are widely used for the control and management of pests in agriculture. However, very little is known about their ef fect on the control of green aphid (Myzus persicae) and whitef ly (Bemisia tabaci). M. persicae and B. tabaci are species that are highly detrimental to the pepper crop due to their sucking habit and because they are disease vectors. This study aimed to evaluate the insecticidal ef fect of extracts of rue (Ruta graveolens), onion (Allium cepa), marigold (Tagetes sp.), and mint (Mentha pulegium) as an ecological alternative for the control of green aphids and whitef lies in pepper crop. Pepper seedlings were transplanted in the f ield and distributed using a randomized block design with f ive treatments (T1: rue extract; T2: onion extract; T3: marigold extract; T4: mint extract; T5: control (Imidacloprid) and three replications. The parameters evaluated were the percentage of incidence, density, and population f luctuation of M. persicae and B. tabaci in the pepper crop, as well as its ef fect on the agronomic and productive variables. The use of botanical extracts of rue, onion, marigold, and mint reduced the incidence and population density of M. persicae and B. tabaci in pepper crops. However, the insecticidal action of rue and marigold were signif icantly evident for B. tabaci (P < 0.05). The population f luctuation of M. persicae and B. tabaci was altered by using botanical extracts. The application of extracts of rue, onion, marigold, and mint did not inf luence the weight and diameter of the fruit, nor af fect the pepper crop (P > 0.05). Therefore, its use should be considered in management programs and agroecological control of these pests.